Structural and kinetic analysis of CO2 sorption on NaNO2-promoted MgO at moderate temperatures - Wang, Ke; Zhao, Youwei; Clough, Peter T.; Zhao, Pengfei; Anthony, Edward J. (Elsevier, 2019)
(200-500 °C) CO2 capture. However, the structure-performance relationship and kinetic characteristics of NaNO2-promoted MgO remain unclear. Here the effects of physical-chemical properties on the CO2 sorption performance of NaNO2-promoted MgO and the sorption kinetics were comprehensively studied to elucidate the detailed role of NaNO2. Samples were characterized by X-ray diffraction, scanning electron microscopy, N2 adsorption, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The sorption kinetics were obtained by isothermal thermogravimetry and elucidated using a double exponential model. Compared with pure MgO and NaNO3-promoted MgO, NaNO2-modified MgO had a lower initial sorption temperature and a unique bimodal sorption characteristic. Characterizations results revealed that such bimodal sorption was due to the presence of double promoters (mixture of NaNO2 and NaNO3) which implies that some of the nitrite was oxidized to nitrate during the preparation process. Deposition of double promoters further reduced the amounts of hydroxide and carbonate species for pure MgO while still preserving more hydroxide and carbonate species on the surface as compared with NaNO3-promoted MgO. The kinetics analysis demonstrated that the double exponential model can well-describe the sorption process for both NaNO3- and NaNO2-promoted MgO, suggesting that the entire sorption occurs as a double process (surface chemisorption and product layer diffusion). Significantly differences were seen from NaNO3-promoted MgO, and the surface chemisorption process of NaNO2-promoted MgO was independent of temperature, which suggests that an increased presence of hydroxide and carbonate species provide more active sites for greatly facilitating surface chemisorption.
Keywords: CO2 capture; NaNO2; NaNO3; MgO